IKLIM ORGANISASI, KEPUASAN, DAN SEMANGAT KERJA GURU SD KATOLIK DI KOTA MERAUKE PAPUA - Basilius Redan Werang (Universitas Negeri Malang, 2015)
Abstract: The purpose of the study was to describe the relation among the organizational climate of the schools and the job satisfaction as well as the spirit at work of the Catholic elementary school teachers in Merauke city, Papua. The samples of the study were 97 (78.86%) out of 123 teachers as the population. The research data was obtained by using questionnaire. The data was analyzed by using SPSS for Windows version 21 software. The results of the study suggested that there was significant relation between organizational climate at schools and the teachers’ job satisfaction as well as their spirit at work. The results also showed the significant relation between the teachers’ job satisfaction and their spirit at work at Catholic elementary schools in Merauke city. Abstrak: Tujuan penelitian ini untuk mendeskripsikan hubungan iklim organisasi sekolah dan kepuasan kerja dengan semangat kerja guru-guru SD Katolik di Kota Merauke, Papua. Sampel penelitian diambil 97 orang (78,86%) dari populasi yang berjumlah 123 guru. Data penelitian diperoleh melalui angket. Pengolahan data menggunakan Program SPSS for Windows versi 21. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara iklim organisasi sekolah dengan kepuasan kerja guru dan semangat kerja guru. Hasil penelitian juga menunjukkan adanya hubungan yang signifikan antara kepuasan kerja guru dengan semangat kerja guru SD Katolik di kota Merauke.